2018
DOI: 10.1002/mp.12839
|View full text |Cite
|
Sign up to set email alerts
|

Material matters: Analysis of density uncertainty in 3D printing and its consequences for radiation oncology

Abstract: If proper quality assurance steps are taken, 3D printed objects can be used accurately and effectively in radiation therapy. It is critically important, however, that the properties of any material being used in patient care be well understood and accounted for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 21 publications
(52 reference statements)
4
92
0
1
Order By: Relevance
“…In previous work, minor differences were found between varying manufacturers and batches for the same material . Nevertheless, we expect the general results to remain stable across platforms.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In previous work, minor differences were found between varying manufacturers and batches for the same material . Nevertheless, we expect the general results to remain stable across platforms.…”
Section: Discussionmentioning
confidence: 59%
“…We did not perform a long‐term measurement that would have investigated a possible drift of the HU values. A study by Craft et al showed that their measured HU values of 3D‐printed material did not change substantially over time and did not strongly depend on the storage environment …”
Section: Discussionmentioning
confidence: 93%
“…For instance, 3D printing was used to fabricate Magnetic Resonance Imaging (MRI) compatible components, electroencephalogram (EEG) electrodes, patient‐specific phantoms for quality assurance (QA) including phantoms with variable radiological properties, as well as immobilization devices and patient‐specific applicator holders for skin brachytherapy . Modeling of tissues by 3D printing is growing, although the radiological properties of 3D printing materials must be critically evaluated for QA or dosimetry applications in radiology or radiation oncology . There are also many applications of 3D printing in sensor technology, including pressure sensors, tactile sensors, displacement sensors, accelerometers, magnetic field sensors, electromagnetic sensors and many others …”
Section: Introductionmentioning
confidence: 99%
“…In the latter, 3D printing has been used for fabrication of parts, fixtures, phantoms and sensors. [4][5][6][7][8][9][10][11] For instance, 3D printing was used to fabricate Magnetic Resonance Imaging (MRI) compatible components, 4 electroencephalogram (EEG) electrodes, 5 patient-specific phantoms for quality assurance (QA) including phantoms with variable radiological properties, [6][7][8][9][10] as well as immobilization devices 11 and patient-specific applicator holders for skin brachytherapy. 12,13 Modeling of tissues by 3D printing is growing, 1 although the radiological properties of 3D printing materials must be critically evaluated for QA or dosimetry applications in radiology or radiation oncology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation